Adsorption and inhibitive impact of 5-[4-(dimethylamino) benzylidene]-1,3-dimethylbarbituric acid on carbon steel corrosion in molar hydrochloric acid solution - El Khalek Khaled M. Abdel; Kamal Shalabi; Mohamed A. Ismail; El Aziz Abd S. Fouda (Zaštita Materijala)
The inhibiting impact of ecofriendly 5-[4-(dimethylamino) benzylidene]-1,3-dimethylbarbituric acid in 1 M HCl on the corrosion for carbon steel has been examined via "weight loss (WL) method, potentiodynamic polarization (PP), electrochemical impedance spectroscopy (EIS), electrochemical frequency modulation (EFM) tests". The attained outcomes exhibit that the investigated compound is excellent inhibitor and its inhibition efficiency (%IE) rises by raising concentration and decreases by raising the temperature. The adsorption of 5-arylidene barbituric acid on the surface of C-steel follows Langmuir isotherm. The adsorption process of the investigated compound is spontaneous and considered as of chemisorption and physisorption type. PP curves revealed that the 5-arylidene barbituric acid derivative is mixed-type inhibitor. Moreover, EIS results confirmed the adsorption of the investigated compound on C-steel surface via increasing on charge transfer resistance (R ct). The IE% of this inhibitor reached to 86.9% at concentration 21×10-6 M according to PP method. Finally, the experimental and theoretical results are in good harmony.